2021
DOI: 10.7573/dic.2020-12-8
|View full text |Cite
|
Sign up to set email alerts
|

The multiple faces of ketamine in anaesthesia and analgesia

Abstract: Objective Ketamine is an anaesthetic agent with a unique dissociative profile and pharmacological effects ranging from the induction and maintenance of anaesthesia to analgesia and sedation, depending on the dose. This article provides information for the clinical use of ketamine in anaesthesia, in both conventional and special circumstances. Methods This is a non-systematic review of the literature, through a PubMed search up to February 2021. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 130 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…Its characteristics that mimic the response to vasopressor effects confer beneficial hemodynamic effects in addition to analgesia and sedation. 2,9 This was also seen in this case, in which a septic shock patient with the addition of a low dose of 0.1 mg/kgBW/hour ketamine could act as analgesia without worsening the patient's hemodynamics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Its characteristics that mimic the response to vasopressor effects confer beneficial hemodynamic effects in addition to analgesia and sedation. 2,9 This was also seen in this case, in which a septic shock patient with the addition of a low dose of 0.1 mg/kgBW/hour ketamine could act as analgesia without worsening the patient's hemodynamics.…”
Section: Discussionsupporting
confidence: 63%
“…Previous research related to the addition of ketamine found that the combination of ketamine-opioid significantly reduced the pain scale score, cumulative morphine consumption, and desaturation events in postoperative patients. 9,10 The use of ketamine in mechanically ventilated patients has shown an increasing trend.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ketamine as an adjunct to multimodal analgesia is well described [2, 20–22]. The advantages include: decreased opioid consumption and tolerance; improved postoperative analgesia; reduced nausea and vomiting; reduction in hyperalgesia; and improved long‐term persistent post‐surgical pain profiles.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been used in premedication. It can be administered orally (5–8 mg/kg), intramuscularly (4–6 mg/kg) or iv (1–2 mg/kg) [ 64 ]. Benefits include its analgesic properties and the ability to cause sedation not associated with respiratory depression [ 65 ].…”
Section: Perioperative Anesthetic Phasesmentioning
confidence: 99%